Sex differences in clinical characteristics and risk factors for disease severity of hospitalized patients with COVID‐19. Issue 2 (8th April 2021) - Wang, Jing‐Jing; Su, Yun‐Juan; Wang, Qi; Cao, Ying; Wang, Ai‐Bin; Ding, Rui; Xie, Wen
Abstract: Recent studies reported sex differences in patients with coronavirus disease‐2019 (COVID‐19). We aim to analyze sex differences in clinical characteristics and risk factors for disease severity of hospitalized patients with COVID‐19 in Beijing. All adults (185 cases) diagnosed with COVID‐19 and admitted to Beijing Ditan Hospital, Capital Medical University were included in samples. The median age of all patients was 41 years. The mean body mass index (BMI) of males was relatively higher compared to females ( p < 0.001). The proportion of male patients with coronary heart disease (CHD), nonalcoholic fatty liver disease (NAFLD), history of smoking and drinking was higher than females. Male patients developed more clinical symptoms, obtained more abnormal laboratory test results, while they were less aware of care‐seeking than female patients. There were no significant differences in clinical complications and outcomes between two groups. Age (odds ratio [OR]: 1.082; 95% confidence interval [CI]: 1.034–1.132; p = 0.001) and BMI (OR: 1.237; 95% CI: 1.041–1.47; p = 0.016) were considered risk factors for refractory pneumonia in multivariate regression analysis. The findings of the current study showed that SARS‐CoV‐2 was more likely to affect older males with comorbidities. Further researches into factors underlying obesity and disease severity may provide mechanistic insight into COVID‐19 development. Abstract : Severity of patients infected in male and female groups on admission. (A) Sankey diagram for general and refractory illness according to the clinical efficacy after hospitalization between male and female groups. (B) Refractory patients in the male group were more than that in female group.